Magnetic features of NiCx carbide with the sphalerite-type defect structure - Nakonechna О.І.; Belyavina, N.N.; Ostapenko, R.V.; Kuryliuk А.М.; Makara, V.A. (Reports of the National Academy of Sciences of Ukraine, 2019)
Magnetic susceptibility of nanoscaled NiCx carbide (x ≤ 0.33) with a defective cubic structure of the sphalerite type (a = 0.3549 nm) synthesized from elemental nickel powder and multiwalled carbon nanotubes in a highenergy planetary ball mill has been studied. The two-stage character of the experimental polytherms of magnetic susceptibility χ(T) is found. It is established that the milling time of the initial Ni-CNT charge in a high-energy ball mill is accompanied by a change in the magnetic characteristics, in particular, by increasing the partial paramagnetic moment and the Curie temperature of the material studied. The revealed effect is explained by the fact that the formation of a crystalline lattice of NiCx carbide at the reaction milling is defined by the carbon atoms, which partially fill the tetrahedral voids of the original nickel lattice, by gradually destroying certain Ni—Ni bonds, thereby increasing the number of electrons with unpaired spins that determine the paramagnetic characteristics of the material obtained.